If matrix A = 1243 such that AX = ϕ,then X is equal to

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

361.

If A = 22- 32, B = 0- 110, then (B- 1A- 1)- 1 is equal to

  • 2- 223

  • 22- 23

  • 2- 322

  • 1- 1- 23


Advertisement

362.

If matrix A = 1243 such that AX = ϕ,then X is equal to

  • 15132- 1

  • 15424- 1

  • 15- 324- 1

  • 15- 12- 14


C.

15- 324- 1

Given, A = 1243 and AX = I      X = A- 1I      X = A- 1Now, A- 1 = 1A3- 2- 41                = 13 - 83- 2- 41                = 15- 324- 1


Advertisement
363.

The inverse of the matrix 10033052- 1 is

  • - 13- 30031092- 3

  • - 13- 3003- 10- 9- 23

  • - 133003- 10- 9- 23

  • - 13- 300- 3- 10- 9- 23


364.

For a invertible matrix A if A(adjA) = 100010 then A =

  • 100

  • - 100

  • 10

  • - 10


Advertisement
365.

If the inverse of the matrix α14- 1231623 does not exist, then the value of α is

  • 1

  • - 1

  • 0

  • - 2


366.

The system 1- 1235- 326axyz = 3b2 has no solutions, if

  • a = - 5, b  5

  • a = - 5, b = 5

  • a  - 5, b = 5

  • a  - 5, b  5


367.

If 3- 1063x1 + - 2x3 = 89, then the value of x is

  • - 38

  • 7

  • - 29

  • None of these


368.

Consider A and B two square matrices of same order. Select the correct alternative.

  • AB must be greater than A

  • 1111 is not unit matrix

  • A + B must be greater than A

  • If AB = 0, either A or B must be zero matrix


Advertisement
369.

The values of x, y and z for the system of equations x + 2y + 3z = 6, 3x - 2y + z = 2 and 4x + 2y + z = 7 are respectively

  • 1, 1, 1

  • 1, 2, 3

  • 1, 3, 2

  • 2, 3, 1


370.

If A and B are square matrices of the same order and A is non-singular, then for a positive integer n, (A-1BA)n is equal to

  • A-nBnAn

  • AnBnA-n

  • A-1BnA

  • n(A-1BA)


Advertisement